Attitude measurement based on imaging ray tracking model and orthographic projection with iteration algorithm - Guo, Xiaoting; Tang, Jun; Li, Jie; Shen, Chong; Liu, Jun (ISA transactions, 2019)
In the field of vision-based attitude estimation, camera model and attitude solving algorithm are the key technologies, which determine the measurement accuracy, effectiveness and applicability. Aiming at this issue, in this paper we probe into the generic imaging model and then develop a corresponding generic camera calibration method using two auxiliary calibration planes. The camera model is named as imaging ray tracking model. Based on the imaging ray tracking camera model and with the knowledge of the calibration parameters, an advanced attitude solving algorithm, imaging ray tracking model and attitude from orthographic projection with iterations algorithm, is deeply investigated, which is inspired by the classical POSIT algorithm. The initial attitude value is provided by the orthographic projection of the object on the two calibration planes and then refined by iteration to approximate the true object attitude. Experimental platform is setup to conduct the imaging ray tracking camera calibration procedure and further evaluate our attitude estimation algorithm. We show the effectiveness and superiority of our proposed attitude estimation algorithm by thorough testing on real-data and by comparison with the POSIT algorithm. •The mapping model is expressed by non-linear high order polynomial.•AOPIT is based on IRT model associating image coordinates and space projection ray.•The specific implementation procedure of the proposed IRT-AOPIT is given in detail.